PERKAWINAN SATU MARGA ETNIS BATAK MANDAILING DI WILAYAH PESISIR TIMUR ACEH (Studi Kasus di Gampong Alue Merbau Pada Tahun 2012-2018) - Subaidah Lubis, Subaidah Lubis (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
The article in this article aims to examine the marriage of one ethnic Batak Mandailing clan that occurred in the east coast of Aceh. This study will discuss the history of the emergence of marriages of one ethnic Batak Mandailing clan in Gampong Alue Merbau. This research is a field research with a qualitative research type and an anthropological historical approach using ethnographic methods with data collection techniques through participant observation, interviews and documentation. Based on the results of the study, the marriage of one ethnic Batak Mandailing clan in Gampong Alue Merbau occurred in 2012 by Pd.Nst with Zb.Nst, in 2015 by Is.Nst with An.Nst and in 2018 by Ak.Nst with Dv.Nst. In 2012 for the first time there was a marriage of one ethnic Batak Mandailing clan in Gampong Alue Merbau, during the marriage process there were no penalties and customary sanctions from the local area, because there were no penalties and customary sanctions for marriage of one clan continued to occur in 2015. and 2018. There are no customary punishments and sanctions received by married couples of the same clan because the people of Gampong Alue Merbau respond to marriages that occur under Islamic law.